Adoption and Perceived Effectiveness of Indigenous Technical Knowledge among Tribal Farmers for Bovine Management: An Exploratory Study - Rai, Chandan Kumar; Singh, Khajan; Lal, Sudhanand Prasad; Arti; Azad, Abul K. (International Journal of Livestock Research, 2019)
The present study aimed at elucidating indigenous technical knowledge (ITK) practices of tribal farmers of Himachal Pradesh where, Gujjar tribe’s population is more and they depend on dairy farming for their livelihood. A total of 110 indigenous practices were documented and only forty three indigenous practices were found scientifically rational which could be further assessed, documented and propagated for the benefit of farming community. Of the total forty three validated practices, eight were related to digestive system; six were related to reproductive system, twenty nine were related to management practices related to limbs, skin and nasal cavity. Two filters were applied to identify the ITK. The first filter was rationality. Only rational ITK practices having rationality score greater than 2.5 were explained in this study. The second filter was mean perceived effectiveness index (MPEI). The perceived effectiveness and adoption rate analysis of these valid forty three ITKs indicated that, fifteen practices were highly effective (>2.5) with more than 50% of adoption rate among the respondents, twenty four were effective (2 to 2.5) and four practices were found as less effective (<2) with their adoption rate of 39% and 18%, respectively.